Deficits in general emotion regulation skills–Evidence of a transdiagnostic factor. Issue 6 (15th December 2017) - Lukas, Christian Aljoscha; Ebert, David Daniel; Fuentes, Hugo Trevisi; Caspar, Franz; Berking, Matthias
Abstract: Objective: Deficits in emotion regulation (ER) skills are discussed as a transdiagnostic factor contributing to the development and maintenance of various mental disorders. However, systematic comparisons of a broad range of ER skills across diagnostic groups that are based on comparable definitions and measures of ER are still rare. Method: Therefore, we conducted two studies assessing a broad range of ER skills with the Emotion Regulation Skills Questionnaire in individuals meeting criteria for mental disorders (N1 = 1448; N2 = 137) and in a general population sample (N = 214). Results: Consistent across the two studies, participants in the clinical samples reported lower general and lower specific ER skills than participants in the general population sample. Also consistent across the two studies, diagnostic subgroups of the clinical samples differed significantly with regard to general and specific ER skills. Conclusion: The studies provide evidence that deficits in ER are associated with various forms of psychopathology. However, mental disorders seem to differ with regard to how strongly they are linked to ER skills.